Quantum-like nonlinear interferometry with frequency-engineered classical light - Romain Dalidet; Anthony Martin; Grégory Sauder; Laurent Labonté; Sébastien Tanzilli (Scientific Reports)
Abstract Quantum interferometry methods exploit quantum resources, such as photonic entanglement, to enhance phase estimation beyond classical limits. Nonlinear optics has served as a workhorse for the generation of entangled photon pairs, ensuring both energy and phase conservation, but at the cost of limited rate and degraded signal-to-noise ratio compared to laser-based interferometry approaches. We present a “quantum-like” nonlinear optical method that reaches super-resolution in classical detection regime. This is achieved by replacing photon-pairs by coherent states of light, mimicking quantum properties through classical nonlinear optics processes. Our scheme utilizes two high-brightness lasers. This results in a substantially greater signal-to-noise ratio compared to its quantum counterpart. Such an approach paves the way to significantly reduced acquisition times, providing a pathway to explore signals across a broader range of bandwidth. The need to increase the frequency bandwidth of the quantum sensor significantly motivates the potential applications of this pathway.